Studying the Effect of Rotor’s Coefficients on a Y-shaped Tri-copter - Al-shamary, Abddullah; Alkamchi, Ahmed; Erçelebi, Ergun (Al-Khwarizmi Engineering Journal, 2025)
Unmanned aerial vehicles (UAVs) are small yet highly capable aircraft widely used in many applications. UAV designs and shapes vary depending on their intended usage. Tri-copters, known for their agility, have three propellers. However, one of their main challenges is yawing, which occurs when the UAV rotates around its z-axis (yaw angle). This yawing issue is a result of the asymmetry in the number of propellers. Unlike quadcopters, which have an even number of propellers, the aerodynamic drag torque produced by the tri-copter’s propellers’ does not cancel out. In this paper, a Y-shaped tri-copter model is tested, modified and compared to address the yawing problem. Aiming to mitigate yawing, two propellers are set to rotate clockwise, whilst the third propeller rotates clockwise. In the first configuration, the force coefficient is set equally for all propellers. In the second configuration, the force coefficient of the counter-clockwise rotating propeller is doubled. The UAV model is controlled by six PIDs associated with feedback linearisation for both configurations—three PIDs for attitude control and three for altitude control. The PIDs are tuned using a genetic algorithm, and the system is simulated in MATLAB Simulink. The proposed configuration demonstrates lower integral time absolute error (ITAE) values, indicating improved UAV performance. The average ITAE values for the Y-shaped model are 0.1553 for the first case and 0.1017 for the second case. The second case shows remarkable tracking in the desired output, with no violation of design limitations (servo angles and motor speeds).